1999
DOI: 10.1016/s0954-6111(99)90072-0
|View full text |Cite
|
Sign up to set email alerts
|

A heated humidifier reduces upper airway dryness during continuous positive airway pressure therapy

Abstract: Upper airway dryness is a frequent side-effect of nasal continuous positive airway pressure (nCPAP) therapy in obstructive sleep apnoea (OSA). In this situation, heated humidification is often used. Alternatively, oily nose drops are frequently applied to relieve dryness. The present study aimed to investigate the efficacy of a heated humidifier in comparison with oily nose drops. Twenty-four OSA patients complaining of serious nCPAP-related upper airway dryness were randomized to 6 weeks of treatment either w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 12 publications
3
28
0
5
Order By: Relevance
“…This is in agreement with the only other randomised controlled study, which has examined the effects of heated humidification administered at the time of nCPAP initiation [21]. Contrary to these observations, the application of heated humidification in patients selected for chronic nasal/ oral symptoms has been shown to improve nasal symptoms, patient comfort and compliance [12,22,23]. Even among unselected groups of patients, such as those included in the current study, heated humidification given over a longer duration (o3 weeks) has been reported to reduce the incidence and severity of nasopharyngeal symptoms [13,14,24,25].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in agreement with the only other randomised controlled study, which has examined the effects of heated humidification administered at the time of nCPAP initiation [21]. Contrary to these observations, the application of heated humidification in patients selected for chronic nasal/ oral symptoms has been shown to improve nasal symptoms, patient comfort and compliance [12,22,23]. Even among unselected groups of patients, such as those included in the current study, heated humidification given over a longer duration (o3 weeks) has been reported to reduce the incidence and severity of nasopharyngeal symptoms [13,14,24,25].…”
Section: Discussionsupporting
confidence: 86%
“…Adverse symptoms of the upper airway are commonly reported with nCPAP [10,11], which can be alleviated with the regular use of heated humidification [12][13][14]. Under experimental conditions, the administration of nCPAP in the presence of mouth leaks leads to the appearance of nasopharyngeal symptoms and a rise in nasal airway resistance (NAR).…”
mentioning
confidence: 99%
“…8 For patients with obstructive sleep apnea, HH ameliorates nasal congestion and mouth dryness, and improves satisfaction. 9,10 The humidification performance of HHs, however, varies according to minute ventilation, F IO 2 , and gas leak around the interface. 11 High ambient temperature and high temperature of the ventilator output also reduce HH performance.…”
Section: Introductionmentioning
confidence: 99%
“…Heated humidification of inspired air attenuates the increase in mucosal blood flow and nasal resistance under experimental conditions [12,13] and adverse upper airway symptoms in OSAS patients chronically treated with nCPAP [9,15,16]. In a recent crossover study, MASSIE et al…”
mentioning
confidence: 99%
“…Heated humidification of inspired air attenuates the increase in mucosal blood flow and nasal resistance under experimental conditions [12,13] and adverse upper airway symptoms in OSAS patients chronically treated with nCPAP [9,15,16]. In a recent crossover study, MASSIE et al [15] demonstrated a small but significant improvement in CPAP use with heated humidified nCPAP (nCPAP-humid) compared to a 2-week washout period but no difference compared to CPAP with a cold passover humidifier [15].…”
mentioning
confidence: 99%